Репрессивная политика советского государства в отношении крымских татар (1921–1941 гг.) - Хаяли, Р. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2009)
The article dedicated to the analysis of repressive politics of higher state authority of the USSR toward Crimean Tatars in 1921–1941.